Factors Affecting the Provision of Sex Education In Early Childhood - Nurhapipa Nurhapipa; Hanifah Hanifah (Institute of Computer Science (IOCS), 2020)
Sex education is the provision of proper knowledge on children and preparing them to adapt better to the sexual attitudes in the future life. Sex education given by parents can be started early, this was due to teach sexuality were strictly necessary from birth to late adolescence stage. The purpose of this study is to obtain in-depth information about factors that affect the provision of sex education in early childhood. The research is a qualitative analytic. Variables such as knowledge, attitude, mother's occupation and source of information. The subjects are three mothers, 1 teacher and principal. The result showed that sex education to children is essentially given by the woman's parents. But with a different understanding and different ways. Early childhood is not necessary to use terms directly to their reproductive organs. Parents need to be informed directly differences in men and women, how the reproductive organs and how relationships between boys and girls. Suggestions that the need for added resources valid information regarding the provision of sex education in early childhood not only for teachers, but also can be given to the elderly, for example in the form of leaflets.